Influencia de las características del terapeuta y del paciente en la constitución de la relación terapéutica (2013)
ABSTRACT: In this paper a brief description of the functions of the patient and the therapist in the constitution of the therapeutic relationship or therapeutic alliance is made. At first the high degree of responsibility of the therapist for being a professional is exposed; subsequently a contrast between the conceptions that have some authors who study clinical psychology in terms of the therapeutic relationship is; some emphasize the role of the therapist, others do it in the function of the patient and others try to locate features on the therapist and the patient on the same level of importance.